Numerical Simulation of Heat Transfer Enhancement in the Paths of Propulsion Systems with Single-Row Spherical and Oval Dimples on the Wall - Sergey Isaev; Dmitry Nikushchenko; Alexandr Sudakov; Nikita Tryaskin; Leonid Iunakov; Alexandr Usachov; Valery Kharchenko (Energies, 2022)
Modeling the vortex intensification of turbulent heat transfer in narrow engine ducts using single-row dimples was carried out within the framework of multi-block computing technologies implemented in a special VP2/3 package. The cases of a rectangular section with the placement of vortex generators—single-row packages of oval and spherical dimples on the initial hydrodynamic section and the section of the stabilized flow are excluded. The connection between the generated vortex structures and the predominant increase in heat transfer compared to the increase in hydraulic losses for various dimple layouts has been established: zigzag, ladder, and centers shifted and in a longitudinal-transverse order. The superiority in heat removal from the thickness with inclined oval dimples is shown—1.23 times compared to spherical ones with a decay in hydraulic resistance by 1.16 times.